A Field Study of Atmospheric Corrosion of Carbon Steel after Short Exposure in Pelabuhan Ratu, West Java Province, Indonesia - PRIYOTOMO, Gadang; PRIFIHARNI, Siska; NURAINI, Lutviasari; TRIWARDONO, Joko; ROYANI, Ahmad; Sundjono, Sundjono; PURAWIARDI, Ibrahim; GUNAWAN, Hadi (Walailak Journal of Science and Technology (WJST), 2021)
The investigation of atmospheric corrosion of mild carbon steel as representative of offshore infrastructure has been carried out in the marine tropical of Pelabuhan Ratu, West Java, Indonesia. They are exposed up to 76 days of periods, and their corrosion rates are determined according to ASTM G1-03. The surface morphology, the elemental compositions and compounds were observed using a scanning electron microscope (SEM), energy dispersive spectroscopy (EDS) and X-ray diffraction (XRD), respectively. The environmental parameters of the test site are monitored during exposure, such as air temperature, relative humidity (RH), airborne salinity and dew temperature. Based on the results, the corrosion rates of steels were 2.79 and 2.8 mpy within the 27 and 76 days exposures, respectively. The presence of chloride deposition on the surface of steel can increase the severity of corrosion. Moreover, the detrimental effect of chloride was observed in rust product, which was covered by an oxygen element. The main phases of rust products present were magnetite (Fe3O4) and hematite (α-Fe2O3.H2O). Several cracks were observed in the rust layer, which tended to exfoliate and lose adherence and protectiveness from further corrosion attack. HIGHLIGHTS The presence of chloride deposition on the surface of steel can increase the severity of corrosion. The severity of corrosion attack mainly depends on the exposure time and some climatic parameters, such as relative humidity (RH), air temperature and chloride airborne. The uniform distribution of the chloride tends to increase the production of ferrous chloride in high RH condition and the aqueous layer deposited on carbon steel. There are two phases on corroded carbon steel such as hematite (α-Fe2O3.H2O) and Magnetite (Fe3O4) after exposure GRAPHICAL ABSTRACT